XBB.1.5 mRNA COVID-19 vaccine protection against inpatient or emergency department visits among adults infected with SARS-CoV-2 JN.1 and XBB-lineage variants - Levy, Matthew E.; Chilunda, Vanessa; Heaton, Phillip R.; McKeen, Deran; Goldman, Jason D.; Davis, Richard E.; Schandl, Cynthia A.; Glen, William B.; McEwen, Lisa M.; Cirulli, Elizabeth T.; Wyman, Dana; Dei Rossi, Andrew; et al. (Frontiers in Immunology, 2025)
As part of a multi-state viral genomic surveillance program, we conducted a case-only analysis to evaluate the effectiveness of XBB.1.5-adapated mRNA vaccines in preventing severe illness among individuals with medically attended SARS-CoV-2 infection. We compared prior receipt of an XBB.1.5-adapted mRNA vaccine between SARS-CoV-2-infected adults with inpatient or emergency department (ED) visits (as a proxy for severe illness) vs those with outpatient visits (as a proxy for mild illness). Among 6,551 patients between September 2023 and January 2024, 6.1% with inpatient or ED visits vs 12.0% with outpatient visits had received XBB.1.5 vaccination (adjusted odds ratio [aOR]=0.41; 95% confidence interval [CI]: 0.32-0.53). This protective association was weaker among JN.1 (aOR=0.62; 95% CI: 0.40-0.96) vs XBB-lineage (aOR=0.28; 95% CI: 0.18-0.43) variant infections (interaction, p=0.003). XBB.1.5 vaccines protect against severe illness, but protection may be weaker against JN.1 vs XBB-lineage variants. This study highlights the need for COVID-19 vaccines to be routinely updated to align with circulating strains and for individuals to stay up to date with recommended vaccines.